THE INFLUENCE OF LEADERSHIP AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE WITH JOB SATISFACTION AS AN INTERVENING VARIABLE AT THE OFFICE OF THE DPRD SECRETARIAT OF UPATEN KAPUAS REGENCY - Ardiansah, Ardiansah; Agustinus Johanes Djohan (Sean Institute, 2021)
Performance as embodiment behavior Work a employees shown as performance Work in accordance with its role in A organization in term time certain . This is to signify performance employee as determinant success as well as continuity life organization . In every organization , human is one of very important component in turn on organization This is . must supported with good performance too because without good performance , organization No will reach the purpose . To That Of course employee need satisfaction For can Work more diligent . To reach good performance , leadership and work environment greatly influence . In addition , job satisfaction is obtained employee become an important aspect , because can impact on its performance which is better good . Therefore that , research This aiming For know influence leadership, work environment and job satisfaction on employee performance . Population in study This is all over employees at the Kapuas Regency DPRD Secretariat Office totaling 60 people . Researchers use saturated sampling technique, meaning that all populations can be used as samples in this study . Data analysis in study This using the path analysis model , because existence intervening variables in the research model This . Research results This show that proven leadership and work environment in a way significant influential positive to job satisfaction. Leadership, work environment and satisfaction proven in a way significant influential positive to employee performance .